The Budegtary Slack Behavior in Ogan Ilir Regency: The effect of Budget Participation, Internal Locus of Control and Environmental Uncertainty as Moderating Variable - Mukhtaruddin; Mikael Mangapu Simarmata; Iwan Efriandy; Shelly F. Kartasari (Indonesian Journal of Business Analytics, 2024)
Budgetary slack (BS) is a deliberate mistake made by the budget creator when preparing the budget. The prevalence of BS is influenced by a number of internal and external factors. This study intends to investigate the factors that lead to BS in the Ogan Ilir Regency, including budgetary participation (BP), internal locus of control (ILC), and environmental uncertainty (EU) as a moderating variable. With a sample size of 68 respondents, questionnaires were distributed to regional organizations in the Ogan Ilir Regency to collect the study's primary data, which were then analyzed using moderated regression analysis (MRA). According to the study's findings, BP has no impact on BS, ILC has a favorable impact on BS, and the EU is unable to moderate the impact of BP and ILC on BS. This study's limitation is that the regression model still does a poor job of describing when BS happens.